Educational games in english to improve oral expression for eighth grade students at the public school Trece de Abril, La Libertad, province of Santa Elena, school year 2014-2015. - González Reyes, Jenniffer (2015)
This Graduation Thesis focused on educational games research to improve oral expression for eight grade students at the public school "TRECE DE ABRIL". The general objective is to develop a proposal of how to implement the use of educational games in the classroom to improve oral expression of the English language. This project has been developed on the basis of the socio-educational approach, qualitative and quantitative and it is supported in a experimental field research, correlation, bibliographic research and field work. After carrying out this research it was concluded that educational games were not used at the “TRECE DE ABRIL” School. For this reason, a proposal of didactic games in the classroom is proposed as an alternative.